How early interventionists support families experiencing vulnerable circumstances: A closer look at family-centered practice. (January 2023) - Spence, Christine M.; Rooks-Ellis, Deborah L.; Brown Ruiz, Amber; Ann Fish, Leigh; Jones-Banahan, Brooklin; O'Grady, Courtney E.; Sulinski, Ella
Highlights: This study provides insight into the family-centered strategies early interventionists (EIs) report using with families experiencing conditions of vulnerability. This study determined that EIs are providing a breadth of family-centered practices (FCP) that are also aligned to the key elements of family centeredness. Providers reported individualizing family services more often than any of the other family-centered key elements, however, it was unclear at times where there was a boundary between creative ways to support families, using research-informed practices within an RBEI model, and utilizing strategies that went beyond the role of an EI. While the strategies described by EIs during home visits seem to align with FCP, much of their work is impacted by other aspects of the EI system, community context, and providers' experiences and biases. Abstract: Guidance from national professional organizations (e.g., the Division for Early Childhood) and professional standards characterize specific practices for the provision of birth through age 2 early intervention services for all families. However, research focused on the family-centered practices (FCPs) that providers use to support families experiencing vulnerability is limited. Therefore, this phenomenological study focused on how early interventionists across disciplines (EIs) described the implementation of services in a rural northeastern state. We conducted nine statewide focus groups with EIs (N = 67) to understand (a) how EIs defined the vulnerable circumstances of the families they serve, and (b) what FCPs EIs report using with families in these identified vulnerable circumstances. Thematic qualitative analysis was used. Results suggest that much of their services align with the key elements of FCP. Providers' use of individualizing services more than any other family centered element is discussed as this may influence aspects of coaching and service delivery.